Integrated HPC Data-log Monitoring System - Mishev, Kostadin; Filiposka, Sonja; Mishev, Anastas (My University, 2016)
Monitoring HPC systems is crucial for the increase of their efficient usage. Integrated monitoring, based on data from various monitoring sources gives a broader picture and enables in depth understanding of the systems, reducing their power consumption and developing of new, highly effective HPC software.
Keywords: HPC, monitoring, efficient usage